The Trend towards Specialization and its Relationship to the Anxiety of the Professional future among special education students at Tafila Technical University - Al-Hawamdeh, Hadeel Mohammed; Al-Khrissat, Ibtihal Mohammad (Journal of Educational and Psychological Sciences, 2023)
The study aimed to know the attitude of special education students towards specialization, investigate professional future anxiety among special education students, and identify the relationship between the trend towards academic specialization and future anxiety and the differences in the direction towards academic specialization and professional future anxiety according to the variables (gender, academic year, cumulative GPA). To achieve the purpose of this study, the descriptive, correlational approach was adopted, and two scales were developed (attitude towards specialization, anxiety about the professional future). The sample included (200) male and female students from the special education major at Tafila Technical University. The results showed that the attitude of the special education students at Tafila Technical University towards their major as a whole was at a high level with an arithmetic average of (2.58), and the level of future professional anxiety was at a moderate level with an arithmetic average of (2.08). It also showed that there were no statistically significant differences in the attitude of special education students towards. Their Specialization was attributed to gender, as the F value reached (0.04) with Statistical Significance (0.84), While the F value for the cumulative average reached (2.58) and statistical significance (0.078), and there was an effect of the academic year between the second and fourth in favour of the second as the F value reached (3.82) and statistical significance (0.011), There are no statistically significant differences in professional future anxiety among special education students due to (gender, academic year, cumulative GPA). There is a statistically significant positive relationship between the trend towards specialization and professional future anxiety. The study recommended the need for parents to give their children the freedom to choose a university major that is in line with their inclinations and desires.